Social media competitive analysis and text mining: a case study in the pizza industry / Elvina Let - Let, Elvina (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
One of the reasons I picked this article is that it is clear that 90% of Malaysians utilize the internet. They must examine customer-generated content on their own social media sites as well as textual information on their competitors' social media sites to acquire a competitive edge and analyze their competitive environment accordingly. The utilization of social media appears to provide a corporation with a more lucrative profit.